2008
DOI: 10.1373/clinchem.2008.103614
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Progression to AIDS and Thrombophilic Abnormalities in HIV Infection

Abstract: Background: HIV-infected patients are at increased risk of venous and arterial thrombosis. We hypothesized that acquired thrombophilic abnormalities that could predispose to thrombosis are most pronounced in patients in advanced stages of HIV infection. Methods: We included 109 consecutive HIV-infected patients in the study and tested them twice for currently known thrombophilic abnormalities at an interval of at least 3 months (median, 3 months; range, 3–12 months). Detailed information was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 42 publications
(50 reference statements)
2
51
1
Order By: Relevance
“…Endothelial dysfunction is also associated with a prothrombotic state,44 and studies which investigated the prothrombotic state in HIV-infected populations showed increased levels of PAI-1 activity and fibrinogen 4,45,46. However, in our study neither the PAI-1 activity nor fibrinogen levels were increased in the HIV-infected subjects, indicating no signs of a prothrombotic state.…”
Section: Discussioncontrasting
confidence: 77%
“…Endothelial dysfunction is also associated with a prothrombotic state,44 and studies which investigated the prothrombotic state in HIV-infected populations showed increased levels of PAI-1 activity and fibrinogen 4,45,46. However, in our study neither the PAI-1 activity nor fibrinogen levels were increased in the HIV-infected subjects, indicating no signs of a prothrombotic state.…”
Section: Discussioncontrasting
confidence: 77%
“…These massive amounts of CXCL4 are deemed to be necessary to trigger the initial phase of hemostasis (24); yet, CXCL4 also exerts immunomodulatory and proinflammatory effects, especially by promoting monocyte activation and differentiation (32). These properties of CXCL4 may be of particular clinical relevance when platelets are abnormally activated in the course of inflammatory processes (13)(14)(15)(16) including HIV-1 infection where a variety of platelet anomalies have been described associated with sustained platelet activation and increased tendency toward thrombosis (17)(18)(19)(20)(21)(22). Thus, CXCL4 may play a dual role in the pathogenesis of HIV-1 disease, on one side by suppressing HIV-1 replication but on the other by fostering immunologic activation, inflammation, and coagulation abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of platelet dysfunctions have been documented during the progression of HIV-1 disease (17), which in some patients lead to severe clinical manifestations such as idiopathic thrombocytopenic purpura (18) and thrombosis (19,20). In addition, platelet alterations, including abnormal platelet activation and apoptosis, are frequently detected in HIV-1-infected individuals even with normal platelet counts (21,22).…”
mentioning
confidence: 99%
“…In a Nederland cohort [4] of 109 patients with HIV, the annual incidences of venous and arterial thrombosis were 5-to 16-fold higher and 2-to 8-fold higher, respectively, than in the healthy population. The median age at the onset of venous thrombosis was 45 years, 17 years earlier than the median age of onset for venous thrombosis in non-HIV-infected patients; and the median age for arterial thrombosis onset was 53 years, a decade earlier than that documented in the Framingham study.…”
Section: Agementioning
confidence: 92%
“…Protein C and protein S deficiencies [5] and increased von Willebrand factor and fibrinogen concentrations [4], have been correlated with immunossuppresion, evidenced by reduced CD4 cell counts. Although the frequency of thrombosis is higher in the presence of lower CD4, there are reports of thrombosis occurring with higher CD4 [15].…”
Section: Cd4 Cell Countmentioning
confidence: 99%